1998
DOI: 10.1038/sj.gt.3300623
|View full text |Cite
|
Sign up to set email alerts
|

Use of SV40 to immunize against hepatitis B surface antigen: implications for the use of SV40 for gene transduction and its use as an immunizing agent

Abstract: We have described a novel gene transfer system, in which subcutaneously into mice every 4 weeks. These mice were replication-incompetent, T antigen-deleted simian virus-40 bled every 2 weeks and their sera assayed for antibody (SV40) is used as the transduction vehicle. We report here activity against HBsAg and SV40. Production of anti-HBs successful immunization using such an SV40-derived viral was measured by ELISA and confirmed by Western blot vector. Hepatitis B surface antigen (HBsAg) cDNA was analysis, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
47
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(50 citation statements)
references
References 29 publications
2
47
1
Order By: Relevance
“…We have shown that transduction using rSV40 vectors is equally effective in unstimulated and stimulated cells, both PBMC and CD34 + cells. 17,18 This observation was confirmed in the current study, and extended to demonstrate that SV(polyTAR) treatment of unstimulated primary human lymphoid cells can protect these cells from HIV-1 challenge. Taken together with the high transduction efficiency (Ͼ95%) 14,17 without selection, this finding suggests that rSV40, and in particular SV(polyTAR) may be an excellent candidate gene delivery vehicle for inhibiting HIV-1 in patients' blood and other lymphoid cells.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…We have shown that transduction using rSV40 vectors is equally effective in unstimulated and stimulated cells, both PBMC and CD34 + cells. 17,18 This observation was confirmed in the current study, and extended to demonstrate that SV(polyTAR) treatment of unstimulated primary human lymphoid cells can protect these cells from HIV-1 challenge. Taken together with the high transduction efficiency (Ͼ95%) 14,17 without selection, this finding suggests that rSV40, and in particular SV(polyTAR) may be an excellent candidate gene delivery vehicle for inhibiting HIV-1 in patients' blood and other lymphoid cells.…”
Section: Discussionsupporting
confidence: 83%
“…17,18 This observation was confirmed in the current study, and extended to demonstrate that SV(polyTAR) treatment of unstimulated primary human lymphoid cells can protect these cells from HIV-1 challenge. Taken together with the high transduction efficiency (Ͼ95%) 14,17 without selection, this finding suggests that rSV40, and in particular SV(polyTAR) may be an excellent candidate gene delivery vehicle for inhibiting HIV-1 in patients' blood and other lymphoid cells. Recent reports indicate that adoptive transfer of modified pbmc or T cells may be an important area of development for the control of viral infections and other diseases; 29,30 the currently reported data suggest that rSV40 gene delivery may be facilitate such therapies.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…35 They also elicit no detectable immune response by normal animals and so can be used to deliver multiple transgenes over time and in sequence. [49][50][51] The ability of rSV40 vectors to deliver long-term transgene expression to mostly quiescent liver cells has been illustrated in murine models, in vivo: immunochemical staining carried out 7 weeks after administration of SV(BUGT) showed that X60% of hepatocytes continued to express the BUGT transgene. 6 Expression continued undiminished for X18 months.…”
Section: Ns5amentioning
confidence: 99%